Masalah Psikososial Anak dengan Penyakit Kanker Selama Pandemi COVID-19 - Septri Nadya; Hellena Deli; Wasisto Utomo (Poltekkes Kemenkes Semarang, 2021)
Background: psychosocial problems are problems that are prone to occur in children with cancer and the COVID-19 pandemic can be one of the factors that exacerbates the psychosocial problems of children with cancer.Pupose: this study aims to describe the psychosocial problems of children with cancer during the COVID-19 pandemic.Methods: the design of this research is descriptive with the number of respondents as many as 28 people. The sampling technique in this research is purposive sampling. This study uses a questionnaire that has been tested for validity and reliability before. The data analysis used in this research is univariate analysis.Results: the results showed that the majority of 15 respondents (53.6%) had negative psychosocial values. The results also showed that 19 respondents (67.9%) experienced anxiety, 16 respondents (57.1%) received poor social support, 17 respondents (60.7%) had social problems, 15 respondents (53.6%) ) experienced symptoms of depression and 15 respondents (53.6%) had a bad body imageConclusion: the description of the psychosocial problems of children with cancer during the COVID-19 pandemic shows that most of the respondents have negative psychosocial outcomes.